Consumer Reactions to Price Discount and Store Atmosphere on Shopping Behavior in Modern Retail Industry - Wardana, Candra Kusuma; Siska Kumalasari; Anton Agus Setyawan (Universitas 45 Surabaya, 2023)
Understanding on what factors which drive customer behavior is crucial for business owners. This study analyzes the effect of discounts and store atmosphere on impulse purchasing decisions. The study was conducted in modern retail business which involved 150 respondents. The sampling method used is a purposive sampling method with the criteria that consumers have experience shopping in modern retail and have knowledge of products in modern retail. Hypothesis testing was used multiple linear regression with SPSS ver. 22. The results showed that price discounts and store atmospheres had a significant effect on impulse purchasing decisions in modern retail business. Creating strategic marketing plan on price deduction and designing impressive store atmosphere is critical in order to increase the impulsive buying and reach the sales target.